دراسة تأثير الخطط الخمسية الزراعية على إنتاج المحاصيل الاستراتيجية في سورية - القمح أنموذجًا- - علي, علاوي; صقر, ابراهيم; محمود, محمد; خدّام, علي (Latakia University Journal -Biological Sciences Series, 2019)
تأتي أهمية هذا البحث من خلال تحليل مساحة، وإنتاج، محصول القمح في ضوء الخطط الخمسيّة الزراعيّة المرسومة على المستوى الكلّي، بهدف التنبؤ بتغيراتهما خلال الفترة من 2019 إلى 2025. لقد أنجز البحث بالاعتماد على منهج الوصفي _التحليلي، ومنهج التحليل الكمي القياسي، والمعطيات الثانوية المأخوذة من البيانات الرسمية، وغير الرسمية، لَدَى وزارة الزراعة والاصلاح الزراعي، والمكتب المركزي للإحصاء، وبيانات منظمة الزراعة والأغذية التابعة للأمم المتّحدة (FAO)؛ والمركز الوطني للسياسات الزراعيّة، وصندوق النقد العربي، ومنظمة التجارة العالمية، ومنظمة الأمم المتحدة للتجارة والتنمية(الاونكتاد). وبيّنت نتائج البحث أنّ المساحة المزروعة بمحصول القمح سوف تزداد بمعدّل نمو سنوي قدره 0.8% خلال السنوات القادمة(2018-2025) بدرجة ثقة 95%، وأنّ جميع القيم المُتنبّأ بها حتى عام 2025 تكون محصورة بين الحدّين الأدنى والأعلى، أي أنّ احتمال وقوع القيم خارج حدود الثقة هو 5%، وذلك باستخدام أنموذج ( ,0,01) ARIMA. كما أظهرت النتائج أنّ كمية إنتاج القمح الكلي في سورية سوف تزداد بصورة تدريجية(بمعدّل نمو سنوي 2.8%) خلال السنوات القادمة(2019-2025) بدرجة ثقة 95%، وأنّ جميع القيم المُتنبّأ بها حتى عام 2025 تكون محصورة بين الحدّين الأدنى والأعلى، أي أنّ احتمال وقوع القيم خارج حدود الثقة هو 5%، وذلك باستخدام أنموذج ( ,0,01) ARIMA. The importance of this research is the analysis of the area, production of the wheat crop, and in light of the five-year agricultural plans drawn at the macro level. Aiming to 2018-2025. The descriptive-analytical approach, and the standard quantitative analysis methodology, have been adopted. The research data were also taken from published and unpublished data with the Ministry of Agriculture and Agrarian Reform, the Central Bureau of Statistics, the Food and Agriculture Organization of the United Nations (FAO), the National Agricultural Policy Center, the Arab Monetary Fund, the World Trade Organization, the United Nations Conference on Trade and Development (UNCTAD). It was found that the cultivated wheat crop area will increase annual growth rate of (0.8%) in th e coming years (2019-2025) degree of confidence of 95%, and that all the predicted values ​​until the year 2025 to be sandwiched between upper and lower limits, ie, the probability of occurrence values ​​outside The confidence limits is 5%, using the ARIMA (0.01) model. The total quantity of wheat production in Syria will increase gradually (2.8% annual growth rate) in the coming years (2019-2025) with a confidence level of 95%, and that all the predicted values ​​up to 2025 will be confined between the lower and upper limits, Values ​​beyond the confidence limits is 5%, using the ARIMA (0,0,1).